WATER–SALT BALANCE AND DYNAMICS OF THE SALINIZATION PROCESS IN IRRIGATED LANDS (ANALYSIS USING THE SALDMOD/INTERACT MODEL) - Shermatov Yormat; Nasirova Malika; Zukhal Sultanovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: Salinization remains one of the major constraints to sustainablecrop production in irrigated regions, where improper water management and high groundwater tables accelerate salt accumulation in soils. This study investigates thewater–salt balance and the temporal dynamics of soil salinity in irrigated lands using the SaldMod/INTERACT modeling framework. The model was applied to simulate soilmoisture regimes, groundwater–surface water interactions, and salt transport processesunder varying irrigation, drainage, and climatic conditions. Field data on soil texture, groundwater depth, irrigation volumes, and salinity levels were incorporated to calibrate and validate the simulations. The results reveal critical periods of salt accumulation driven by evapotranspiration and insufficient leaching, while effective drainage and optimized irrigation scheduling significantly reduced salinity buildup. Model outputs demonstrate strong agreement with observed field measurements, indicating the reliability of SaldMod/INTERACT for assessing salinity risks and evaluating management scenarios. Overall, the findings highlight the necessity of integrated water management strategies to maintain a favorable water–salt balance and prevent long-term degradation of irrigated soils